A conjecture on the nature and evolution of consciousness. Issue 2 (2nd July 2016) - Rogers, Terence W.; Friedberg, Ahron
Abstract : The profound importance of consciousness in everyday life suggests that it is a natural and necessary outgrowth of our biological heritage. In this paper we offer a conjecture that consciousness is a deep property of biological life itself. We propose a specific model of how a form of core consciousness could be present in all life forms, and subsequently how each species could create a unique form of consciousness from that common core. We formulate the first consideration as the core consciousness conjecture, and the extension to all animals as the extended core consciousness conjecture.